Evangelização das classes médias e solidariedade com os pobres: o legado de Medellín - Morás, Francisco (Revista Eclesiástica Brasileira, 1998)
Neste artigo, depois de uma breve contextualização histórico-eclesial do Documento de Medellín, o autor oferece uma tríplice análise do Documento. Em primeiro lugar evidencia as principais componentes do projeto de evangelização presentes no documento, em seguida avalia como as classes médias, direta ou indiretamente, entram neste projeto de evangelização, e, por fim, tenta deduzir os níveis de solidariedade com os pobres que das classes médias se espera. Trata-se de uma análise movida pela suspeita de que a solidariedade com os pobres depende, em grande medida, da qualidade da evangelização que for ministrada às classes médias. Abstract: After a brief historical-ecclesiastical contextualization of the document of Medellín, the author, in this article, offers a threefold analysis of the document. In the first place, it evidences the principal components ofthe project for evangelization present in the document, followed by an evaluation on how the middle classes, directly or indirectly, enter into this project of evangelization and, to sum up, a try at deducing the leveis of solidarity with the poor that we can expect from the middle classes. This is about an analysis motivated by the suspician that the solidarity with the poor depends, in great measure, upon the quality of the evangelization that was ministered to the middle classes.